2019
DOI: 10.1080/13607863.2019.1569589
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversity and depressive symptoms among middle-aged and older Chinese: results from China health and retirement longitudinal study

Abstract: Objectives: A number of studies have established the link between childhood adversity (CA) and depression across the life span. This association can be culturally specific, and it remains unclear whether and how different aspects of CA affect depressive symptoms in later life in non-Western societies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…Landes et al ( 2014 ) reported that a lack of parenting and a lower social status in childhood predict more functional limitations or morbidities in older age. Traumatic events in childhood such as physical abuse, sexual abuse, parental death, and bullying victimisation have been found to be associated with older-age anxiety or depression disorder (Chou 2012 ; Draper et al 2008 ; Lund et al 2008 ; Yang et al 2019 ). Verropoulou and Serafetinidou ( 2019 ) and Weinstein ( 2016 ) found that poorer health and a lower socio-economic status are associated with more severe symptoms of affective suffering and motivation and lower functional capability.…”
Section: Discussionmentioning
confidence: 99%
“…Landes et al ( 2014 ) reported that a lack of parenting and a lower social status in childhood predict more functional limitations or morbidities in older age. Traumatic events in childhood such as physical abuse, sexual abuse, parental death, and bullying victimisation have been found to be associated with older-age anxiety or depression disorder (Chou 2012 ; Draper et al 2008 ; Lund et al 2008 ; Yang et al 2019 ). Verropoulou and Serafetinidou ( 2019 ) and Weinstein ( 2016 ) found that poorer health and a lower socio-economic status are associated with more severe symptoms of affective suffering and motivation and lower functional capability.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that children who experience early parental death are taken care of by other family members, a common phenomenon decades ago in China when multiple generations tended to live together [41]. This might have served as a buffering resource for health outcomes amongst Chinese adults who lost their parent(s) during childhood [42].…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirm the importance of living in place where neighbors had close-knit relationships at childhood. Some studies found that childhood adversity had a negative effect on depression in middle and later life [ 11 , 13 , 32 ]. Different from these studies, this study focused on the association between childhood neighborhood relationship and mental health among the middle-aged and older adults.…”
Section: Discussionmentioning
confidence: 99%